Hard turning of AISI D2 steel with cubic boron nitride cutting inserts. (2023) - Kumar, Satish; Tamilselvan, P.; Feroskhan, M.; Doss, Arockia Selvakumar Arockia; Sasikumar, M.; Elango, M.; Sivarajan, S.
Abstract: Industries use heat treated steel for various components due to its strength and other mechanical properties. Usually hardening of machining is carried out by energy and cost intensive grinding process. Recently, hard machining has replaced grinding for certain specific applications. In this study, Cubic boron nitride (CBN) of specification CNMG120408is employed to machine AISI D2 steel of 46 HRC hardness. Nine machining experiments established by L9 orthogonal array were conducted. Surface roughness and cutting force were taken as response variables. From the signal to noise ratio analysis, the optimum combination of cutting process parameters for surface roughness is found out to be 80 m/min (Cutting speed) 0.109 mm/rev (Feed) and 0.1 mm (depth of cut). From Analysis of variance (ANOVA), the share made by every process parameter on the machining performance is found out for this CBN tool-work piece combination. Feed rate has the maximum contribution (56 %) for main cutting force while Cutting speed has the maximum contribution (72 %) for surface roughness. Cutting speed exerts greater influence on surface finish compared to feed rate in hard machining.